Interpretation of Reason as a Configuration of Human Character from the Perspective of the Qur'an - Aria Panji Saputra; Abdul Rasyid Ridho (al-Afkar, Journal For Islamic Studies, 2025)
The Qur'an views humans as being divided into two elements: namely the first material element and the second inmaterial element. The spirit or soul which is material in nature has two types of power: the first is the power of thought which is called 'aql which is centered in the brain (head). These two feelings are called the heart which is centered in the chest. The type of research method that the author used in writing this research is a qualitative method in the nature of library research. Reason is a human privilege given by Allah SWT as a tool for determining truth and error, and reason is also a tool that can change or encourage human character.